KETERAMPILAN WARGA BELAJAR DALAM PEMBELAJARAN ONLINE - Dety Ayu Putri; Suardi Jasma (Jurnal Pendidikan Sepanjang Hayat, 2021)
The purpose of this study was to describe the readiness of citizens to learn the package C program in participating in online learning at PKBM Songgo Langit Bengkulu City. The subjects of this study were three people. This research is a qualitative case study research. Data collection techniques are interview techniques, observation and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. checking the validity of the data using triangulation techniques. The results showed that first, there was the ability of learning citizens to understand and use online learning applications, the ability was included in the cognitive realm. Second, learning citizens had skills in online learning, skills included in the psychomotor realm. Third, the media used in online learning is privately owned and the media is always checked before starting the lesson. Fourth, learning citizens attend and collect assignments on time, and do not cheat during exams and obey the rules. Fifth, in Talang Pauh Village, Bengkulu Tengah District, the network the internet is adequate but during bad weather the network connection is not stable. In online learning, citizens learn to use their own costs for internet quotas